A study of empowerment level in currently married women in western Maharashtra, India - Prabhu, Priya M. (International Journal of Research in Medical Sciences, 2017)
Background: Empowerment of women in all fields constitutes one of the fundamental objectives of development efforts in a region. Laws can support the endeavour of women’s empowerment, but considering the complex cultural beliefs and practices that lie at the root of the imbalance, the effectiveness of such isolated efforts remains doubtful. Present study was planned to assess level of women’s empowerment in western region of Maharashtra with objectives to measure various direct and indirect indicators of women’s empowerment by different background characteristics. Methods: A cross-sectional study using structured questionnaire based interviews was carried out in female outpatients in tertiary care hospital. The sample of 300 currently married women in reproductive age-group was selected by systematic random sampling. Results: Out of 360 women majority belonged to Hindu religion (65%), and households of middle standard of living (71.7%) and 76.6% women were married below age of 21. 38.3% women were always involved in household decision making. Regarding freedom of movement, 38.3% women have complete freedom whereas 41.7% women have some control over economic resources. But only 30% women have personal savings. 60% women have favourable attitude towards girls’ education, and only 33.3% women defy domestic violence. Conclusions: There are significant divergences in the direct and indirect indices of women’s empowerment and there is much scope for improvement in self-esteem of women.